2008
DOI: 10.1159/000185628
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-Brain Natriuretic Peptide Independently Predicts Protein Energy Wasting and Is Associated with All-Cause Mortality in Prevalent HD Patients

Abstract: Background: N-terminal pro-brain natriuretic peptide (NT-proBNP) has been demonstrated to be associated with cardiovascular disease (CVD) and mortality in end-stage renal disease patients. We hypothesized that common confounders, such as protein-energy wasting (PEW) and inflammation could modulate this relationship. Methods: NT-proBNP was measured in 222 prevalent hemodialysis (HD) patients (55.4% male, mean age 66 years, range 51–74) using commercial ELISA. Levels were related to clinical characteristics, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 73 publications
1
28
0
1
Order By: Relevance
“…But most importantly, a strong correlation between NT-proBNP and CRP levels is found (figure 1), suggesting an association between left-ventricular filling pressure and inflammation among patients with CKD. This association between left-ventricular filling pressure and inflammation among CKD patients has been confirmed in subsequent years (Guo et al, 2009;Jacobs et al, 2010;Paniagua et al, 2010). Otherwise, the same studies and other authors (Booth et al, 2010) observed a relationship between cardiac and inflammatory biomarkers and volume overload.…”
Section: Association Between Inflammation Overhydratacion and Cardiasupporting
confidence: 53%
See 1 more Smart Citation
“…But most importantly, a strong correlation between NT-proBNP and CRP levels is found (figure 1), suggesting an association between left-ventricular filling pressure and inflammation among patients with CKD. This association between left-ventricular filling pressure and inflammation among CKD patients has been confirmed in subsequent years (Guo et al, 2009;Jacobs et al, 2010;Paniagua et al, 2010). Otherwise, the same studies and other authors (Booth et al, 2010) observed a relationship between cardiac and inflammatory biomarkers and volume overload.…”
Section: Association Between Inflammation Overhydratacion and Cardiasupporting
confidence: 53%
“…Probably, this pathophysiological mechanism partly explains the high levels of BNP detected among patients with CKD. In fact, several studies have observed an association between natriuretic peptide levels and echocardiographic data of left ventricular hypertrophy and dysfunction among patients with CKD (Guo et al, 2009;Paniagua et al, 2010;Zocali et al, 2001). Natriuretic peptide levels among patients with CKD predict death, as it occurs in patients with heart failure and normal renal function.…”
Section: Association Between Inflammation Overhydratacion and Cardiamentioning
confidence: 99%
“…Finally, the measurement of the ankle-brachial index, a well-known screening tool for PVD, had been demonstrated to have a prognostic significance of cardiovascular survival in chronic HD patients [37]. Moreover, both arterial stiffness and N-terminal pro-brain natriuretic peptide were found to be associated with CAVD and all-cause mortality in HD patients [38, 39]. The lack of those thorough examinations in our study indicates more comprehensive investigations should be expected.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical use of NT-proBNP in optimizing the treatment of patients with chronic heart failure has been shown by Januzzi et al [5]. NT-proBNP levels are influenced by factors such as sex, age, fluid status, nutritional status, body mass index, thyroid status and renal function [6,7,8]. NT-proBNP increases with the worsening of renal function and is more strongly related to the glomerular filtration rate than BNP [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a single measurement of NT-proBNP is a predictor of mortality in hemodialysis patients [10,11,14,15] and that NT-proBNP levels are higher in dialysis patients with protein energy wasting (PEW) and/or inflammation [8]. Furthermore, using longitudinal data we have previously reported a strong relationship between inflammation and comorbidity, in particular congestive heart failure, whereas variation of NT-proBNP is reported to be low in nonrenal patients with stable heart failure [16,17].…”
Section: Introductionmentioning
confidence: 99%